Pengaruh Tingkat Kemiskinan, Indeks Pembangunan Manusia, dan Tingkat Pengangguran Terbuka terhadap Indeks Kebahagiaan Masyarakat Indonesia: Analisis Data Sekunder BPS Tahun 2021 - Klara Innata Arishanti (Jurnal Ilmu Sosial dan Humaniora, 2026)
Happiness has become an important indicator for assessing community well-being beyond conventional economic measures. This study aimed to analyze the influence of poverty rate, Human Development Index (HDI), and Open Unemployment Rate (OUR) on the Happiness Index in Indonesia using secondary data published by Statistics Indonesia (BPS) in 2021. This research employed a quantitative explanatory approach with a saturated sampling technique involving 34 provinces. Data were analyzed using descriptive statistics and multiple linear regression with IBM SPSS Statistics version 26. The results indicated that poverty rate, HDI, and OUR simultaneously had no significant effect on the Happiness Index (F = 0.698; p = 0.560). Partially, poverty rate (p = 0.196), HDI (p = 0.450), and OUR (p = 0.524) also showed no significant effect. The coefficient of determination (R² = 0.065) indicated that the three independent variables explained only 6.5% of the variation in the Happiness Index, while the remaining 93.5% was influenced by other factors outside the model. These findings suggest that subjective well-being in Indonesia is shaped not only by socioeconomic conditions but also by psychological, social, and environmental factors..